Dioscorea flabellispina (Dioscoreaceae), a new endangered species from the Brazilian Atlantic Rainforest - Couto, Ricardo Sousa; Lopes, Rosana Conrado; Braga, João Marcelo Alvarenga (Phytotaxa, 2015)
Dioscorea flabellispina is endemic to small, low elevation fragments of the Atlantic Rainforest in southeastern Brazil, occurring on rocky outcrops in the states of Rio de Janeiro and Espirito Santo. Based on the number and form of thorns present on the stem (5–8 thorns with a fan-like form at the node), this new species is easily recognizable morphologically and possesses characteristics unique to the Neotropical Dioscorea. Presenting only a few individuals in each population, this rare and endangered species is only known from three sites surrounded by a vegetation matrix degraded by human impact and overrun by invasive alien species. Dioscorea flabellispina does not occur in any officially protected area in Brazil, placing the species at increased risk. Herein we present the morphological description of this species, including a discussion of its ecology, distribution, and conservation status.